Pemanfaatan AI (Artificial Intellegence) Secara Etis dalam Pembelajaran Mahasiswa pada Program Studi S1 Akuntansi Universitas Mataram - Indria Puspitasari Lenap; Nina Karina Karim; Siti Atikah (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
The use of Artificial Intelligence (AI) in education has continued to grow and has become an important part of supporting students’ learning activities. AI provides various benefits, including helping students access information, understand learning materials, complete academic tasks, and improve learning efficiency. However, the use of AI without adequate ethical understanding may lead to several problems, such as plagiarism, excessive dependence on technology, decreased critical thinking skills, and the use of inaccurate information. Therefore, this community service activity aimed to improve students’ AI literacy and ethical awareness in using AI wisely and responsibly. This activity was conducted with undergraduate accounting students at the Faculty of Economics and Business, University of Mataram, through several stages consisting of a pre-test, AI literacy education, and a post-test. The educational materials covered the ethics of AI use, strategies for utilizing AI in academic activities, and the risks and misuse of AI. The methods used included interactive lectures and material dissemination to encourage students to understand AI concepts critically and practically. The results showed an improvement in students’ understanding and awareness regarding the ethical use of AI. Students became more aware of the importance of verifying information, using proper references, and utilizing AI as a learning support tool rather than a substitute for the thinking process. In addition, there was a positive change in students’ patterns of AI usage toward more responsible and constructive use. Overall, this educational activity was effective in improving AI literacy and fostering more critical, ethical, and responsible academic attitudes in the digital era